What's Spurious, What's Real? Measuring the Productivity Impacts of ICT at the Firm-Level - Thomas Hempell (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
In order to assess the productivity effects of information and communication technologies (ICT), regressions based on cross?sectional firm?level data may yield unreliable results for the commonly employed production function framework. In this paper, various estimation biases and econometric strategies to overcome their sources are discussed. The effects are illustrated on the basis of a representative set of panel data for German service firms. The application of a suited SYS?GMM estimator yields evidence for significant productivity effects of ICT which are substantially smaller though than those suggested by cross?section or pooled OLS estimates.
Keywords: D24; C23; C81; L80; 330; Productivity; Information and Communication Technologies; Production Function Estimation; Panel Data; Services; Informationstechnik; Produktivität; Computergestütztes Verfahren; Produktionsfunktion; Ökonometrisches Modell; Schätzung; Dienstleistungssektor; Theorie; Deutschland